Experimental study on the durability properties of Shahabad stone waste as partial replacement of coarse aggregate in concrete. (2021) - Soundarya, N.
Abstract: The effect of using Shahabad stone waste as partial replacement of coarse aggregates on durability properties is investigated in this work. This work aims at utilizing Shahabad stone waste in concrete as a building material in concrete to increase the strength and durability properties of the concrete. Shahabad stone waste was used as partial replacement of coarse aggregates. The stones used are calcareous in nature. The dressing of this calcareous stone produces huge amount of solid waste of sizes which range from 5 mm to 150 mm size. As projected by TIFAC [1] in the year 2005 about 188.6 million tonnes of solid waste was produced by mining and dressing sites, out of which 1/3rd of the total waste produced is Shahabad stone waste in India. The coarse aggregates in concrete is replaced with 20 mm size Shahabad stones. Experimental study was done by replacing 10%, 20%, 30% and 40% of coarse aggregates using Shahabad stones in M25 grade concrete. Durability tests were conducted and the results are presented here. It was found out that the results have proven that 30% is the optimum replacement in terms of strength as well as durability and hence Shahabad stone waste can be successfully used as partial replacement to coarse aggregate in concrete.